"Zombie trucks": Cleaning up the working dead. Issue 3 (June 2018) - Kaur, Dipleen; Krall, Jenna R.
Abstract : "Zombie" or "glider trucks" bring old engines back to life, but a rule change that requires those engines to meet current emissions standards is stuck in limbo.Dipleen Kaur andJenna R. Krall discuss the impact this delay may have on pollution and health Abstract : "Zombie" or "glider trucks" bring old engines back to life, but a rule change that requires those engines to meet current emissions standards is stuck in limbo. Dipleen Kaur and Jenna R. Krall discuss the impact this delay may have on pollution and health.